Creative mathematics : exploring children's understanding - Upitis, Rena Brigit (Routledge, 1997)
Exploring the ways in which maths skills can be learned through cross-curricular projects on arts and music, this book presents maths as a meaningful and exciting subject which holds no fear for children.